ANALYSIS OF POROSITE-NEUTRON (NPHI) LOGGING DATA FROM THE KINKASI FIELD: THE CASE OF THE G UP, F AND E HORIZONS OF THE CENOMANIAN RESERVOIR (D.R. CONGO COASTAL BASIN) - Munene Asidi Djonive; Kanika Mayena Thomas; Manteko Matondo Emmanuel; Nsitu Nsitu Djeskin; Biduaya Ngalamulume Jeff; Bangama Kabongo Augustin (Romanian Journal of Petroleum & Gas Technology)
Since the discovery of hydrocarbon deposits in the DR Congo Coastal Basin in general, and in the Kinkasi field in particular, several development wells have been drilled with a view to optimising the economic value of the reserves evaluated. Despite the large number of wells drilled in this onshore area of the Coastal Basin and a multitude of development studies, it should be noted that production is stagnating at around 10,000 barrels per day. This report is a considerable contribution to addressing these major concerns. Certainly, with the advancement of technology through the creation of supercomputers and software, these reprocessings can prove important in that they can bring to light certain information that previously went unnoticed. As well as highlighting the importance of modelling the petrophysical parameters of a reservoir in the development of an oil field, this subject provides assistance to the Production Engineer, insofar as it makes it possible to visualise, from the desktop with some software such as Microsoft Excel 2010 for the calculation of certain data with a view to representing them in the form of tables and graphs, the Geographic Information System (ArcGis 10.3) for representing the study area and drawing up maps of the spatial distribution of porosity-neutron horizons, areas of interest that could be the subject of in-depth studies ((location of new wells).